Development of an ELISA using the surface antigen one protein to detect for Streptococcus suis infection - Chiêu, Trần Thị Bích; Hoa, Võ Minh; Uyên, Phan Nhã; Hùng, Trần Mạnh; Châu, Nguyễn Văn Vĩnh; Hoa, Ngô Thị (Vietnam Journal of Biotechnology, 2016)
Streptococcus suis (S. suis) is one of the most important pathogens to cause acute bacterial meningitis in Viet Nam and other Asia countries including Thailand and Hongkong. We investigated the potential of using ELISA with the SAO protein as antigen to detect for S. suis specific sero positive. An SAO specific antibody collected from hyperimmunised rabbits was employed to develop the prototype ELISA. S. suis and other bacterial pathogens were used to validate the sensitivity and specificity of this method. This prototype ELISA was validated using serum samples collected from meningitis patients to evaluate its application in sero surveillance. The prototype ELISA protocol included a 0.1mg/well concentration of the cloned and purified SAO-M antigen; the primary antibody, anti SAO-M protein, and secondary antibody were used at the dilution of 1:500 and 1:10000, respectively.  Rabbit antisera contained specific SAO-M antibody with 100% specificity and titer of >1:16000.  Validating the prototype ELISA using serum samples collected from patients infected with S. suis and other common pathogens for bacterial meningitis in Vietnam showed the specificity of 95% and sensitivity of 90%. Our current results confirmed the initial success in developing the prototype ELISA in diagnosis for S. suis infections and the potential for its future application